(untitled) (Palimpsesto, 2017)
This article aims to make a contribution to the understanding of the notion of "life" in the ancient Israel. This issue is explored from various angles. A first moment focuses on life and its concreteness in Adam as a living being par excellence. A second moment investigates the meaning of life as an accomplishment in this present world and the community of Israel. These themes predispose to the conception of God as author of life and as the one who is truly alive. After all, and as Psalm 146.2 puts it, life is to be celebrated as a gift: “I’ll praise the Lord with my life”.